Preferensi tenggeran burung di Pulau Jawa sebagai rujukan untuk konservasi ex-situ: Kajian pustaka - Azmi, Haibah; Janitra, Fikrah; Norine, Jennifer; Priyandoko, Didik; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The rate of growth of society in Indonesia, especially on the island of Java, has meant that much land has been converted into residential areas. This causes several bird species to lose their habitat and become endangered, so conservation is needed as an effort to preserve them. This research aims to determine the perching preferences of birds on the island of Java, making it easier to create a living environment that suits their natural environment. This research uses qualitative methods through a literature review of literature sources, articles, and scientific journals. The IUCN Red List page is used to determine the scope of the aves species discussed in this article, namely the island of Java, and to find out the aves' habitat so that their perch preferences can be found. Three different categories of perches were obtained, namely texture, height, and perch diameter, with the assumption that these data could be translated to create artificial perches for ex-situ conservation.